Creatininium 4-nitrobenzoate – A phase matchable organic nonlinear optical material with large laser-induced damage threshold value for optoelectronics applications. (September 2018) - Thirumurugan, R.; Babu, B.; Anitha, K.; Chandrasekaran, J.
Graphical abstract: Highlights: Creatininium 4-nitrobenzoate (C4NB), an organic NLO single crystal was grown. C4NB crystal exhibits good optical transparency and high thermal stability (220 °C). A low value of dielectric constant at higher frequencies has been obtained. Phase matching second harmonic generation behavior was studied. Large laser damage threshold value of 3.6 GW/cm 2 has been achieved. Abstract: A promising organic nonlinear optical (NLO) material of creatininium 4-nitrobenzoate (C4NB) was grown as single crystals using slow evaporation solution technique. The grown crystal was crystallized in orthorhombic system of acentric space group, P21 21 21 . The crystalline nature was analyzed by powder X-ray diffraction study. The molecular structure was evidently established by using 1 H and 13 C NMR spectral analysis. The UV-vis-NIR spectrum showed high optical transparency of C4NB crystal in Vis-NIR region with lower cut-off wavelength at 353 nm. Thermal analysis revealed that C4NB crystal was thermally stable up to 225 °C. The dielectric behavior was studied at different temperatures as a function of frequency varies from 50 Hz to 5 MHz. The mechanical nature and photoconductivity behaviour were carried out effectively for grown crystal. The NLO phase matching and laser-induced damage threshold (LDT) characteristics of C4NB crystal was done by Nd:YAG laser and compared with other organic crystals. All these characterizations and their results recognized that grown crystal may be exploited for optoelectronics applications in near future.